Harvesting time related to milling quality of four irrigated rice cultivars - Infeld, José Alceu; Silveira Junior, Paulo (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this study was to find the best harvesting time as related to moisture content and milling quality of four lowland rice cultivars, namely: Lebonnet, Bluebelle, EEA-406 and IRGA-408. The research was carried out at Pelota, RS, Brazil, in the growing seasons of 1979/ 80, 1980/81 and 1981/82. Starting 20 days and ending 40 days after full heading, grain samples were harvested each five days and its moisture content and milling quality evaluated. 'Lebonnet' showed the highest percentage (64.9) of head rice 34 days after full heading 18.5% of moisture); 'Bluebelle' showed the highest percentage (64.9%) of head rice 38 days after full heading (19.5% of moisture; both EEA-406' and 'IRGA-408' showed the highest percentage (59.6 and 57.6, respectively) of head rice 36 days after full heading (24 and 22% of moisture, respectively).